Pancreatitis biliar aguda en gestante de 27 semanas. - Sipion Sanchez, Gisleyner Maoly (2020)
The spectrum of pancreatitis in pregnancy varies from mild to severe pancreatitis, within this we can find Counterpancreatitis with necrosis, pancreatic abscesses, development of pancreatic pseudocyst to multisystem failure. This pathology during pregnancy is favored by biliary stasis that predisposes it to acquire more lithogenic properties. Epidemiologically in Ecuador per year it occurs in 1 per 12,000 pregnancies. The objective is to evaluate compliance with the care protocols for acute pancreatitis present in the 27-week pregnant patient, the purpose is to prevent organ failure and complications. The diagnostic methodology is based on the application of anamnesis, physical examination and complementary tests such as complete blood count, blood biochemistry, C-reactive protein, O`sullivan's test, assessment by breast Score and ultrasound. Infectious antibiotics, analgesics and surgical treatment are used, which is reserved for two scenarios: in the case of complications of the disease itself, such as necrosis of the pancreas and the other scenario is when you try to correct the basic biliary disease (cholelithiasis), it is that is, cholecystectomy in most cases performed with minimally invasive techniques (laparoscopy). The importance of prenatal control is emphasized from the moment it is known, even more so when we have predominant factors such as obesity and gestational diabetes which lead to a high-risk pregnancy, due to not going to a health unit to take the proper controls, in this case the patient could have severe complications if she did not receive the appropriate treatment.